2020
DOI: 10.3389/fpsyg.2020.00956
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Body Exposure Therapy for Anorexia Nervosa. A Case Report With Follow-Up Results

Abstract: Objective: Exposure-based therapies such as mirror exposure may help to improve the results of classic cognitive behavioral therapy in anorexia nervosa (AN). Virtual reality (VR)-based procedures provide interesting novelties for targeting body-related concerns. This study aimed to provide preliminary evidence of the usefulness of a VR body exposure therapy in a patient diagnosed with AN. Method: Fear of gaining weight (FGW), body anxiety, drive for thinness, body image disturbances, body mass index and body-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 24 publications
1
59
1
Order By: Relevance
“…Consequently, focusing on the primary conditioned stimulus (weight gain) rather than on the secondary ones, such as eating, may be an effective strategy. As has been reported, VR embodiment-based techniques are a successful way to change body image disturbances in patients with AN [ 39 , 40 , 41 ]. We propose going one step further.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, focusing on the primary conditioned stimulus (weight gain) rather than on the secondary ones, such as eating, may be an effective strategy. As has been reported, VR embodiment-based techniques are a successful way to change body image disturbances in patients with AN [ 39 , 40 , 41 ]. We propose going one step further.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, among AN patients, Keizer et al [ 39 ] found that owning a skinny virtual body significantly reduced the perceived body size in AN patients, as well as in healthy participants. These results were later replicated by two case report studies, which showed that VR embodiment-based techniques (e.g., using a visuo-tactile stimulation procedure) allowed the modification of body image disturbances either in the short term [ 40 ] or over several sessions [ 41 ].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Obviously, to be realistic, the VR model tries to mimic the brain model as much as possible: the more the VR model is similar to the brain model, the more the individual feels present in the VR world" (p. 89). These features allow clinical XR platforms (e.g., VR) to structure, augment, and/or replace the patient's bodily experience in novel ways that can be used in clinical applications [37][38][39][40]. Further, clinical XR provides novel embodied paths to assess patient brain function [41] by directly targeting the processes underpinning real-world behaviors [42][43][44].…”
Section: But Why Is This Happening?mentioning
confidence: 99%